Effect of FSW Parameters on The Microstructure and Mechanical Properties of T-joints between Dissimilar Al-Alloys - El-Sayed Seleman , Mohamed M.; Z. Ahmed, Mohamed M; M. Ramadan, Rashad; A. Zaki, Basant (International Journal of Integrated Engineering, 2022)
The main purpose of this research is to develop T-joints between the aluminum AA 2024-T4 and AA 7075-T6 using friction stir welding.  The effect of tool geometries, tool traveling speed, and rotational rate in the welded T-joints were investigated and discussed. Three different tools were used with different shoulder to pin ratios 3.28, 3.36, and 4.31. After optimization, the best tool dimension has used with the different rotational and welding speeds. Three tool traverse speeds of 50, 75, and 100 mm/min were used. Two rotation rates of 800 rpm and 1000 rpm were applied. After FSW, at a number of the above FSW parameters' combinations, macrostructure and microstructure analyses were done using optical microscopy. In order to have an insight into the mechanical properties, hardness measurements and tensile testing were carried out. Using small shoulder to pin ratio produced visually unacceptable T-joint. Opposite happened by using the tool with 4.31 of shoulder to pin ratio. Furthermore, the results showed sound T-welds with no obvious defects at high rotational rate of 1000 rpm with the two used traveling speeds. Asymmetric temperature distribution was observed between the two sides, advance side (AS) and retreating side (RS)